The Stigma of Addiction - Pavlovsky, Federico (Revista del Hospital Italiano de Buenos Aires, 2026)
Less than 10% of people with addictions receive treatment, with women facing greater inequality. Stigma, structural barriers, and lack of adequate care deepen the problem. This editorial calls for integrated care, a gender-sensitive approach, and active strategies to bring treatment closer to those who need it most.